2018
DOI: 10.1186/s12967-018-1379-9
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and genomic characterizations of patient-derived esophageal squamous cell carcinoma xenograft models using biopsies for treatment optimization

Abstract: BackgroundSquamous cell carcinoma is the dominant type of esophageal cancer in China with many patients initially diagnosed at advanced stage. Patient-derived xenografts (PDX) models have been developed to be an important platform for preclinical research. This study aims to establish and characterize PDX models using biopsy tissue from advanced esophageal cancer patients to lay the foundation of preclinical application.MethodsFresh endoscopic biopsy tissues were harvested from patients with advanced esophagea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 58 publications
(50 reference statements)
3
26
0
Order By: Relevance
“…Tumor cell line xenografts were established by subcutaneous injection of 2 × 10 6 cells from in vitro cultures. Patient-derived xenograft (PDX) models were established in our lab according to previous studies 44 . Tumors were measured with fine calipers twice a week.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor cell line xenografts were established by subcutaneous injection of 2 × 10 6 cells from in vitro cultures. Patient-derived xenograft (PDX) models were established in our lab according to previous studies 44 . Tumors were measured with fine calipers twice a week.…”
Section: Methodsmentioning
confidence: 99%
“…Xanthohumol was reported to attenuate lung and breast cancer cell growth and the anticancer effects of xanthohumol were associated with the downregulation of EGFR, STAT3, Notch and nuclear factor‐κB (NF‐κB) . However, the mechanisms underlying its chemopreventive/therapeutic effects remain unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Xanthohumol was reported to attenuate lung and breast cancer cell growth and the anticancer effects of xanthohumol were associated with the downregulation of EGFR, STAT3, Notch and nuclear factor-κB (NF-κB). 21,41,42 However, the mechanisms underlying its chemopreventive/therapeutic effects remain unresolved. The present study focused on identifying a direct target of xanthohumol and we found that xanthohumol inhibited AKT kinase activity ( Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations